Electronic transport and low frequency noise in atomically thin graphene and hexagonal boron nitride two-dimensional heterostructure field effect transistors - Behera, Aroop K (My University, 2024)
Field Effect Transistors (FETs) form the basis for modern integrated circuits (ICs), that are the building blocks of every computing and communication device. The need for faster and energy efficient microprocessors has enabled continuous development of novel device architectures with the state-of-the art micro/nano-fabrication technologies, aiming for a transistor feature size of ≈3 nm and beyond. However, scaling down the device dimension below 3 nm brings added challenges due to various fundamental physical limits, thus demanding a paradigm shift in materials and device fabrication techniques. Two-dimensional (2D) atomically thin materials along with their heterostructures have shown exceptional electrical, optical, mechanical, thermal, and chemical properties that provide avenues to innovate newer and smaller devices with promise for delivering higher performance and energy efficiency. However, fundamental understanding of carrier transport in terms of their microscopic origin and their scattering mechanisms are necessary to elucidate the device physics of such 2D transistors. This dissertation work delves into the design and fabrication of 2D heterostructure graphene field effect transistor (2D-HGFET) devices, understanding their electrical transport properties by investigating various carrier scattering mechanisms, and characterize the fluctuations in the carrier transport by studying the electrical noise also called as 1/f low-frequency noise. This dissertation work provides the first comprehensive study on the correlation between electrical transport and 1/f noise in 2D-HGFET devices relating to graphene and hexagonal boron nitride materials. Both noise analysis and transport properties were used to estimate the trap energy levels in the devices. The use of hexagonal boron nitride as the substrate and encapsulation material to a graphene conductive channel has been shown to produce high mobility transistors due to its similar crystal structure with minimal lattice mismatch, reduced impurities, lower interface trap states, and high difference in electrical conductivity. Furthermore, it has also been demonstrated that one-dimensional electrical contacts (called ”1D-edge contacts”) to 2D-HGFETs provide high current injection with low contact resistances that are necessary for high performance devices. This dissertation employs 2D-HGFETs with 1D-edge contacts to study the electrical transport, 1/f noise, and their correlation. Despite extensive transport measurements on heterostructure transistor devices, the coupling between atomic layers, particularly hexagonal boron nitride (hBN) and graphene, in terms of the phonon modes of hBN on electronic transport in graphene is in infancy. In this study, temperature dependent electrical transport and low frequency noise measurements were performed to understand the effect of phonon modes in hBN/graphene/hBN heterostructure and its conductance as 2D-HGFET device channel. The effect of longitudinal acoustic (LA) phonons in graphene conductive channel is found to be the dominant carrier scattering mechanism at lower temperatures, whereas remote interfacial polar phonons in hBN dominate carrier scattering at elevated temperatures. Furthermore 1/f noise in 2D-HGFETs were modeled to the carrier-phonon scattering and the average density of trap states in hBN/graphene/hBN heterostructure systems were calculated from which the trap energy (both electronic and hole) were extracted. The origin, impact, and engineering of phonons on the electronic and noise characteristics constitute the most significant contribution of this dissertation and it provides further avenues for the investigation of engineered 2D heterostructures and their devices.
Keywords: hBN-graphene-hBN heterostructure FET; Edge-contacted FET; Remote interfacial phonons; 1/f noise